2016
DOI: 10.21608/ejnf.2016.74871
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Phytoestrogens on Livestock Production: A Review

Abstract: hytoestrogens, polyphenolic compounds, are one of the major plant secondary metabolites found abundantly in animal diets. However, these phytochemicals play initial important roles in plant growth, development and maintenance. They also have many biological roles in animal body, affecting their productivity. The richest sources of phytoestrogens in animal diets are legumes, particularly, soybeans and clover. These plants often comprise substantial part of animal feed, thus presenting a potential source of phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…produce significant quantities of non-steroidal secondary metabolites known as phytoestrogens [ 5 ]. Phytoestrogens are synthesized by various enzymatic pathways depending on the structural group [ 6 ] and are known to play an important role in plant defense against predation and herbivory [ 6 ], as well as plant growth and maintenance [ 7 ]. Plants tend to accumulate phytoestrogens during times of environmental stress and disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…produce significant quantities of non-steroidal secondary metabolites known as phytoestrogens [ 5 ]. Phytoestrogens are synthesized by various enzymatic pathways depending on the structural group [ 6 ] and are known to play an important role in plant defense against predation and herbivory [ 6 ], as well as plant growth and maintenance [ 7 ]. Plants tend to accumulate phytoestrogens during times of environmental stress and disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gjorgovska et al (2016) fed laying hens added isoflavones (1,000 mg/kg) and observed an increase of 0.08 in the laying rate compared to the control group (0.80 vs. 0.72), but no further increase was seen with the addition of greater amounts. In contrast, the performance of other animal species have been decreased by ingestion of red clover due to its high phytoestrogen content, in particular in sheep due to fertility problems (Hashem and Soltan, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The ovary is a nonconventional target tissue of estrogen, in addition to that expression of estrogen receptor type alpha is very low or cannot be measured in contrast, beta-estrogen receptor expression is high in ovarian tissue (Saji, Jensen et al, 2000) The Affinity of genistein to beta-type estrogen receptors is approximately 20-30 times greater than of alpha-estrogen receptors compared with estradiol (Morito, Hirose et al, 2001). The similarities between estrogen (17βEstadiol) and phytoestrogen genistein at the molecular level allow the latter to reduce the effect of estrogen or counteract its effect when associated with estrogen receptors and prevent its effect (Yildiz 2005;Hashem and Soltan 2016). At the same time, the level of estrogen in the blood increases and the increase in the concentration of estrogen stimulates the production of sex hormone-binding globulin (SHBG), This leads to faster removal of sex hormones, including estrogens, Thus, target cells need estrogen more than phytoestrogen provides , In addition, the hypothalamus-ovarian-ovarian axis leads to negative feedback with high estrogen levels to control the secretion of hormones released…”
Section: Discussionmentioning
confidence: 99%
“…The similarities between estrogen (17βEstadiol) and plant estrogen at the molecular level can reduce the latter effect of estrogen or metabolise its effect, as it can bind to the estrogen receptor to increase its effect or prevent its association with its inhibitory effect (Yildiz 2005 andHashem andSoltan 2016). Although the phytoestrogens are not exactly identical to normal female estrogen, they mimic their biochemical properties, amazingly.…”
Section: Introductionmentioning
confidence: 99%